Active material layer, electrode and lithium ion secondary battery

By incorporating a second active material with a higher reaction potential in a trace amount within the active material layer, the discharge rate characteristics of lithium ion secondary batteries are improved, enabling faster charge and discharge performance.

JP7601558B2Active Publication Date: 2024-12-17TDK CORP
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2020046602
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-03-17
Publication Date
2024-12-17
Estimated Expiration
2040-03-17

AI Technical Summary

Technical Problem

Existing lithium ion secondary batteries lack excellent discharge rate characteristics, which affect their ability to perform rapid discharge.

Method used

The active material layer in the battery is composed of a first active material as the main component and a second active material as a subcomponent, with the second active material having a higher reaction potential and being present in a trace amount, promoting a concentration gradient for lithium ions and improving discharge rate characteristics.

Benefits of technology

The lithium ion secondary battery exhibits enhanced discharge rate characteristics due to the presence of the second active material, facilitating faster charge and discharge reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007601558000007
    Figure 0007601558000007
  • Figure 0007601558000001
    Figure 0007601558000001
  • Figure 0007601558000002
    Figure 0007601558000002
Patent Text Reader

Abstract

To provide a lithium ion secondary battery superior in discharge rate characteristic.SOLUTION: The active material layer comprises at least an active material and a binder. The active material includes a first active substance of a main component, and a second active substance which is a subcomponent different from the first active substance in composition. The proportion of the first active substance is 60% of a total quantity of the active substances or more and less than 100%, and the proportion of the second active substance is more than 0% of the total quantity of the active substances and less than 5%.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an active material layer, an electrode, and a lithium ion secondary battery. [Background technology]

[0002] Lithium ion secondary batteries are also widely used as power sources for mobile devices such as mobile phones and notebook computers, hybrid cars, etc. With the development of these fields, higher performance is being demanded of lithium ion secondary batteries.

[0003] For example, Patent Document 1 discloses a lithium secondary battery in which a coating made of a mixture of two or more types is formed on the surface of the positive electrode. Patent Document 1 discloses that the coating suppresses decomposition of the electrolyte due to a reaction between the active material and the electrolyte, thereby improving cycle characteristics.

[0004] For example, Patent Document 2 describes a positive electrode in which an active material is coated with a specific metal, intermetallic compound, or oxide. It describes that the metal coating the active material absorbs oxygen, thereby improving the safety of the battery. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 8-236114 [Patent Document 2] Japanese Patent Application Publication No. 11-16566 Summary of the Invention [Problem to be solved by the invention]

[0006] Discharge rate characteristics are one of the indicators of battery performance. Discharge rate is the speed required to reach the final voltage from full charge. Discharge rate characteristics are the ratio of the discharge capacity when the discharge rate is increased to the discharge capacity when discharging at a specified discharge rate. A battery with excellent discharge rate characteristics is capable of rapid discharge.

[0007] The present disclosure has been made in consideration of the above problems, and has an object to provide a lithium ion secondary battery having excellent discharge rate characteristics. [Means for solving the problem]

[0008] In order to solve the above problems, the following means are provided.

[0009] (1) An active material layer according to a first aspect has at least an active material and a binder, the active material comprising a first active material as a main component and a second active material as a subcomponent having a composition different from that of the first active material, the proportion of the first active material being 60% or more and less than 100% of the total active material, and the proportion of the second active material being greater than 0% and less than 5% of the total active material.

[0010] (2) In the active material layer according to the above aspect, the first active material may be secondary particles formed by agglomerating a plurality of primary particles, and the second active material may be primary particles.

[0011] (3) In the active material layer according to the above aspect, the particle size of the first active material may be 0.6 to 1.5 times the particle size of the second active material.

[0012] (4) In the active material layer according to the above aspect, the second active material may have a higher reaction potential than the first active material.

[0013] (5) In the active material layer according to the above aspect, the second active material is Li a Co 1-y M yO2 (1), where a satisfies 0.8≦a≦1.2, y satisfies 0≦y<0.5, and M may be at least one of Ni, Mn, Fe, Mg, Zr, Al, Ti, Zn, Cu, Ca, and Na.

[0014] (6) An electrode according to a second aspect includes a current collector and the active material layer according to the above aspect laminated on at least one surface of the current collector.

[0015] (7) A lithium ion secondary battery according to a third aspect includes the electrode according to the above aspect. Effect of the Invention

[0016] The lithium ion secondary battery according to the above aspect has excellent discharge rate characteristics. [Brief description of the drawings]

[0017] [Figure 1] 1 is a schematic diagram of a lithium ion secondary battery according to a first embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Hereinafter, the embodiments will be described in detail with reference to the drawings as appropriate. The drawings used in the following description may show characteristic parts in an enlarged scale for the sake of convenience in order to make the characteristics easier to understand, and the dimensional ratios of each component may differ from the actual ones. The materials, dimensions, etc. exemplified in the following description are merely examples, and the present invention is not limited thereto, and may be appropriately modified and implemented within the scope of the present invention.

[0019] "Lithium-ion secondary battery" Fig. 1 is a schematic diagram of a lithium ion secondary battery according to a first embodiment. The lithium ion secondary battery 100 shown in Fig. 1 includes a power generating element 40, an exterior body 50, and a non-aqueous electrolyte (not shown). The exterior body 50 covers the periphery of the power generating element 40. The power generating element 40 is connected to the outside via a pair of connected terminals 60, 62. The non-aqueous electrolyte is contained within the exterior body 50.

[0020] (Power generation element) The power generating element 40 includes a positive electrode 20, a negative electrode 30, and a separator 10.

[0021] <separator> The separator 10 is sandwiched between the positive electrode 20 and the negative electrode 30. The separator 10 separates the positive electrode 20 from the negative electrode 30, and prevents a short circuit between the positive electrode 20 and the negative electrode 30. Lithium ions can pass through the separator 10.

[0022] The separator 10 has, for example, an electrically insulating porous structure. Examples of the separator 10 include a monolayer or laminate of a film made of a polyolefin such as polyethylene or polypropylene, a stretched film of a mixture of the above resins, and a fibrous nonwoven fabric made of at least one constituent material selected from the group consisting of cellulose, polyester, polyacrylonitrile, polyamide, polyethylene, and polypropylene.

[0023] The separator 10 may be, for example, a solid electrolyte. The solid electrolyte is, for example, a polymer solid electrolyte, an oxide-based solid electrolyte, or a sulfide-based solid electrolyte. The polymer solid electrolyte is, for example, a polyethylene oxide-based polymer in which an alkali metal salt is dissolved. The oxide-based solid electrolyte is, for example, Li 1.3 Al 0.3 Ti 1.7 (PO4)3 (Nasiconic type), Li 1.07 Al 0.69 Ti 1.46 (PO4)3 (glass ceramics), Li 0.34 La 0.51 TiO 2.94 (Perovskite type), Li7La3Zr2O 12 (Garnet type), Li 2.9 PO 3.3 N 0.46 (amorphous, LIPON), 50Li4SiO4·50Li2BO3 (glass), 90Li3BO3·10Li2SO4 (glass ceramics). Sulfide-based solid electrolytes include, for example, Li 3.25 Ge 0.25P 0.75 S4 (crystal), Li 10 GeP2S 12 (crystal, LGPS), Li6PS5Cl (crystal, argyrodite type), Li 9.54 S 1.74 P 1.44 S 11.7 Cl 0.3 (crystal), Li 3.25 P 0.95 S4 (glass ceramics), Li7P3S 11 (glass ceramics), 70Li2S 30P2S5 (glass), 30Li2S 26B2S3 44LiI (glass), 50Li2S 17P2S5 33LiBH4 (glass), 63Li2S 36SiS2 Li3PO4 (glass), and 57Li2S 38SiS2 5Li4SiO4 (glass).

[0024] <Positive electrode> The positive electrode 20 has a positive electrode current collector 22 and a positive electrode active material layer 24. The positive electrode active material layer 24 is formed on at least one surface of the positive electrode current collector 22.

[0025] [Positive electrode current collector] The positive electrode current collector 22 is, for example, a conductive plate material, for example, a thin metal plate made of aluminum, copper, nickel, titanium, stainless steel, or the like.

[0026] [Cathode active material layer] The positive electrode active material layer 24 includes, for example, a positive electrode active material, a conductive assistant, and a binder.

[0027] The positive electrode active material can reversibly absorb and release lithium ions, desorb and insert (intercalate) lithium ions, or dope and dedope lithium ions and counter anions.

[0028] The positive electrode active material is composed of at least two or more active materials. The positive electrode active material includes, for example, a first active material as a main component and a second active material as a subcomponent. The abundance ratio of the second active material is extremely small compared to the first active material. The second active material is present in only a trace amount in the positive electrode active material layer 24.

[0029] The proportion of the first active material in the entire positive electrode active material is 60% or more and less than 100%, preferably 60% or more and less than 99%, more preferably 80% or more and less than 99%, and even more preferably 96% or more and less than 98%. The proportion of the second active material in the entire positive electrode active material is more than 0% and less than 5%, preferably 0.5% or more and less than 4.5%, and more preferably 1% or more and less than 4%. When the positive electrode active material is composed of the first active material and the second active material, the total proportion of the first active material and the second active material is 100%. When there are three or more types of positive electrode active materials, the total proportion of the first active material and the second active material is less than 100%.

[0030] The first active material has a different composition from the second active material. The reaction potential of the second active material is, for example, higher than the reaction potential of the first active material. The reaction potential is the electric potential energy at which the intercalation reaction of lithium occurs, and is the reaction potential relative to the equilibrium potential of Li. For example, the reaction potentials of spinel compounds (hereinafter referred to as LMO), manganese phosphate compounds (hereinafter referred to as LMP), lithium cobalt oxide (hereinafter referred to as LCO), nickel-cobalt-manganese ternary compounds (hereinafter referred to as NMC), nickel-cobalt-aluminum ternary compounds (hereinafter referred to as NCA), lithium iron phosphate (hereinafter referred to as LFP), sulfur-based compounds, and lithium titanium oxide (hereinafter referred to as LTO) satisfy the relationship of LMO>LMP>LCO>NMC≒NCA>LFP>sulfur-based compounds>LTO.

[0031] The second active material is, for example, Li a Co 1-y M y It is a compound represented by the formula: O2···(1), where a satisfies 0.8≦a≦1.2, y satisfies 0≦y<0.5, and M is at least one of Ni, Mn, Fe, Mg, Zr, Al, Ti, Zn, Cu, Ca, and Na. In the above formula (1), when y=0, it is LCO.

[0032] For example, the first active material may be a secondary particle, and the second active material may be a primary particle. A secondary particle is a particle formed by agglomeration of multiple primary particles. For example, when observing a cross section of a particle with a transmission electron microscope (TEM), if a grain boundary is visible within the particle, it is a secondary particle, and if the grain boundary is not visible, it is a primary particle.

[0033] The particle size of the first active material is, for example, 0.6 to 1.5 times, preferably 0.9 to 1.1 times, of the particle size of the second active material. Here, the particle size is the average particle size of 10 or more particles. If the particles are irregular, the particle size is half the sum of the length of the major axis and the length of the minor axis. If secondary particles are formed, the particle size is the particle size of the secondary particles.

[0034] The binder binds the positive electrode active materials together in the positive electrode active material layer 24. A known binder can be used. The binder is, for example, a fluororesin. Examples of the fluororesin include polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), tetrafluoroethylene-perfluoroalkylvinyl ether copolymer (PFA), ethylene-tetrafluoroethylene copolymer (ETFE), polychlorotrifluoroethylene (PCTFE), ethylene-chlorotrifluoroethylene copolymer (ECTFE), polyvinyl fluoride (PVF), etc.

[0035] In addition to the above, the binder may be, for example, vinylidene fluoride-based fluororubber such as vinylidene fluoride-hexafluoropropylene-based fluororubber (VDF-HFP-based fluororubber), vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene-based fluororubber (VDF-HFP-TFE-based fluororubber), vinylidene fluoride-pentafluoropropylene-based fluororubber (VDF-PFP-based fluororubber), vinylidene fluoride-pentafluoropropylene-tetrafluoroethylene-based fluororubber (VDF-PFP-TFE-based fluororubber), vinylidene fluoride-perfluoromethylvinylether-tetrafluoroethylene-based fluororubber (VDF-PFMVE-TFE-based fluororubber), or vinylidene fluoride-chlorotrifluoroethylene-based fluororubber (VDF-CTFE-based fluororubber).

[0036] The conductive assistant enhances the conductivity between the positive electrode active materials in the positive electrode active material layer 24. Examples of the conductive assistant include carbon powders such as carbon black, carbon nanotubes, carbon materials, metal fine powders such as copper, nickel, stainless steel, and iron, mixtures of carbon materials and metal fine powders, and conductive oxides such as ITO. The conductive assistant is preferably a carbon material such as carbon black. When sufficient conductivity can be ensured with the active material alone, the positive electrode active material layer 24 does not need to contain a conductive assistant.

[0037] The positive electrode active material layer 24 may also contain a solid electrolyte or a gel electrolyte. The solid electrolyte may be, for example, the same as that which can be used in the separator.

[0038] <Negative electrode> The negative electrode 30 includes, for example, a negative electrode current collector 32 and a negative electrode active material layer 34. The negative electrode active material layer 34 is formed on at least one surface of the negative electrode current collector 32.

[0039] [Negative electrode current collector] The negative electrode current collector 32 is, for example, a conductive plate material. The negative electrode current collector 32 may be the same as the positive electrode current collector 22.

[0040] [Negative electrode active material layer] The negative electrode active material layer 34 contains a negative electrode active material. Optionally, it may also contain a conductive material, a binder, and a solid electrolyte.

[0041] The negative electrode active material may be any compound capable of occluding and releasing ions, and known negative electrode active materials used in lithium ion secondary batteries can be used. Examples of the negative electrode active material include metallic lithium, lithium alloys, graphites (natural graphite, artificial graphite) capable of occluding and releasing ions, carbon nanotubes, non-graphitizable carbon, graphitizable carbon, carbon materials such as low-temperature calcined carbon, semi-metals or metals such as aluminum, silicon, tin, and germanium that can combine with metals such as lithium, SiO x (0 < x < 2), amorphous compounds mainly composed of oxides such as tin dioxide, lithium titanate (Li4Ti5O 12 ) and the like are particles.

[0042] The negative electrode active material layer 34 may contain, for example, silicon, tin, and germanium as described above. Silicon, tin, and germanium may exist as single elements or as compounds. The compounds are, for example, alloys, oxides, etc. As an example, when the negative electrode active material is silicon, the negative electrode 30 may be called an Si negative electrode. The negative electrode active material may be, for example, a mixed system of a single or compound of silicon, tin, germanium and a carbon material. The carbon material is, for example, natural graphite. Also, the negative electrode active material may be, for example, one in which the surface of a single or compound of silicon, tin, germanium is coated with carbon. The carbon material and the coated carbon enhance the conductivity between the negative electrode active material and the conductive assistant. When the negative electrode active material layer contains silicon, tin, and germanium, the capacity of the lithium ion secondary battery 100 increases.

[0043] The negative electrode active material layer 34 may contain, for example, lithium as described above. The lithium may be metallic lithium or a lithium alloy. The negative electrode active material layer 34 may be metallic lithium or a lithium alloy. The lithium alloy is, for example, an alloy of lithium and one or more elements selected from the group consisting of Si, Sn, C, Pt, Ir, Ni, Cu, Ti, Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Sb, Pb, In, Zn, Ba, Ra, Ge, and Al. As an example, when the negative electrode active material is metallic lithium, the negative electrode 30 may be called a Li negative electrode. The negative electrode active material layer 34 may be a lithium sheet.

[0044] The negative electrode 30 may not have the negative electrode active material layer 34 during fabrication, and may comprise only the negative electrode current collector 32. When the lithium-ion secondary battery 100 is charged, metallic lithium is precipitated on the surface of the negative electrode current collector 32. Metallic lithium is elemental lithium from which lithium ions have been precipitated, and the metallic lithium functions as the negative electrode active material layer 34.

[0045] The conductive material and binder may be the same as those in the positive electrode 20. The binder in the negative electrode 30 may be, in addition to those listed in the positive electrode 20, for example, cellulose, styrene-butadiene rubber, ethylene-propylene rubber, polyimide resin, polyamide-imide resin, acrylic resin, etc. The cellulose may be, for example, carboxymethyl cellulose (CMC).

[0046] (Terminal) The terminals 60 and 62 are connected to the positive electrode 20 and the negative electrode 30, respectively. The terminal 60 connected to the positive electrode 20 is a positive electrode terminal, and the terminal 62 connected to the negative electrode 30 is a negative electrode terminal. The terminals 60 and 62 are responsible for electrical connection to the outside. The terminals 60 and 62 are made of a conductive material such as aluminum, nickel, or copper. The connection method may be welding or screwing. The terminals 60 and 62 are preferably protected with insulating tape to prevent short circuits.

[0047] (Exterior body) The power generating element 40 and the non-aqueous electrolyte are sealed inside the exterior body 50. The exterior body 50 prevents the non-aqueous electrolyte from leaking to the outside and prevents moisture and the like from entering the lithium-ion secondary battery 100 from the outside.

[0048] 1, the exterior body 50 has a metal foil 52 and a resin layer 54 laminated on each side of the metal foil 52. The exterior body 50 is a metal laminate film in which the metal foil 52 is coated on both sides with a polymer film (resin layer 54).

[0049] For example, aluminum foil can be used as the metal foil 52. A polymer film such as polypropylene can be used as the resin layer 54. The materials constituting the resin layer 54 may be different between the inside and outside. For example, a polymer with a high melting point such as polyethylene terephthalate (PET) or polyamide (PA) can be used as the material for the outside, and polyethylene (PE), polypropylene (PP), etc. can be used as the material for the polymer film on the inside.

[0050] (Non-aqueous electrolyte) The non-aqueous electrolyte is sealed in the exterior body 50 and impregnates the power generating element 40 . The non-aqueous electrolyte solution includes, for example, a non-aqueous solvent and an electrolyte. The electrolyte is dissolved in the non-aqueous solvent.

[0051] The non-aqueous solvent contains, for example, a cyclic carbonate and a chain carbonate. The cyclic carbonate solvates the electrolyte. The cyclic carbonate is, for example, ethylene carbonate, propylene carbonate, and butylene carbonate. The cyclic carbonate preferably contains at least propylene carbonate. The chain carbonate reduces the viscosity of the cyclic carbonate. The chain carbonate is, for example, diethyl carbonate, dimethyl carbonate, and ethyl methyl carbonate. The non-aqueous solvent may also contain methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, 1,2-dimethoxyethane, 1,2-diethoxyethane, and the like.

[0052] The non-aqueous solvent may contain, for example, a cyclic carbonate or a chain carbonate in which some of the hydrogen atoms are substituted with fluorine, such as fluoroethylene carbonate or difluoroethylene carbonate.

[0053] The volume ratio of the cyclic carbonate to the chain carbonate in the non-aqueous solvent is preferably 1:9 to 1:1.

[0054] The electrolyte is, for example, a lithium salt. The electrolyte is, for example, LiPF6, LiClO4, LiBF4, LiCF3SO3, LiCF3CF2SO3, LiC(CF3SO2)3, LiN(CF3SO2)2, LiN(CF3CF2SO2)2, LiN(CF3SO2)(C4F9SO2), LiN(CF3CF2CO)2, LiBOB, etc. The lithium salt may be used alone or in combination of two or more. From the viewpoint of the degree of ionization, it is preferable that the electrolyte contains LiPF6.

[0055] The non-aqueous solvent may have, for example, a room-temperature molten salt. The room-temperature molten salt is a salt obtained by combining a cation and an anion and is liquid even at temperatures below 100° C. Since the room-temperature molten salt is a liquid consisting of only ions, it has strong electrostatic interactions and is characterized by being non-volatile and non-flammable.

[0056] Examples of the cationic component of the room-temperature molten salt include nitrogen-based cations containing nitrogen, phosphorus-based cations containing phosphorus, sulfur-based cations containing sulfur, etc. These cationic components may be contained alone or in combination of two or more kinds. Examples of the nitrogen-based cation include linear or cyclic ammonium cations such as imidazolium cation, pyrrolidinium cation, piperidinium cation, pyridinium cation, and azoniaspiro cation. The phosphorus-based cation includes linear or cyclic phosphonium cations. Examples of sulfur-based cations include linear or cyclic sulfonium cations. As the cationic component, the nitrogen-based cation N-methyl-N-propyl-pyrrolidinium (P13) is particularly preferred because it has high lithium ion conductivity and wide redox resistance when a lithium imide salt is dissolved therein.

[0057] The anion component of room temperature molten salt is AlCl4 - , NO2 - , NO3 - , I - , BF4 - , PF6 - , AsF6 - , SbF6 - , NbF6 - , TaF6 - , F(HF) 2.3 - , p-CH3PhSO3 - , CH3CO2 - , CF3CO2 - , CH3SO3 - , CF3SO3 - , (CF3SO2)3C - , C3F7CO2, C4F9SO3 - , (FSO2)2N - (Bis(fluorosulfonyl)imide) (FSI), (CF3SO2)2N - (Bis(trifluoromethanesulfonyl)imide) (TFSI), (C2F5SO2)2N - (Bis(pentafluoroethanesulfonyl)imide), (CF3SO2)(CF3CO)N - ((Trifluoromethanesulfonyl)(trifluoromethanecarbonyl)imide), (CN)2N - (dicyanoimide), etc. These anion components may be used alone or in combination of two or more.

[0058] "Method of manufacturing lithium-ion secondary batteries" First, the positive electrode 20 is prepared. The positive electrode 20 is prepared by mixing a positive electrode active material, a binder, and a solvent to prepare a paste-like positive electrode slurry. At least two types of positive electrode active material, a first active material and a second active material, are prepared. The amount of the second active material mixed with respect to the first active material is very small. There is no particular restriction on the method of mixing these components constituting the positive electrode slurry, and there is also no particular restriction on the mixing order. Next, the positive electrode slurry is applied to the positive electrode current collector 22. There is no particular restriction on the application method. For example, a slit die coating method or a doctor blade method can be used.

[0059] Next, the solvent in the positive electrode slurry applied onto the positive electrode current collector 22 is removed. The removal method is not particularly limited. For example, the positive electrode current collector 22 on which the positive electrode slurry is applied is dried under an atmosphere of 80°C to 150°C. Next, the obtained coating film is pressed to densify the positive electrode active material layer 24, thereby obtaining the positive electrode 20. As the pressing means, for example, a roll press machine, a hydrostatic press machine, or the like can be used.

[0060] Next, the negative electrode 30 is prepared. The negative electrode 30 can be prepared in the same manner as the positive electrode 20. The negative electrode 30 is prepared by mixing a negative electrode active material, a binder, and a solvent to prepare a paste-like negative electrode slurry. The negative electrode slurry is applied to a negative electrode current collector 32 and dried to obtain the negative electrode 30. When the negative electrode active material is metallic lithium, lithium foil may be attached to the negative electrode current collector 32.

[0061] Next, the prepared positive electrode 20 and negative electrode 30 are laminated so that the separator 10 is located between them to prepare the power generating element 40. When the power generating element 40 is a wound body, the positive electrode 20, the negative electrode 30, and one end side of the separator 10 are wound around the axis.

[0062] Finally, the power generating element 40 is enclosed in the exterior body 50. A non-aqueous electrolyte is injected into the exterior body 50. After the injection of the non-aqueous electrolyte, the pressure is reduced, heating, etc. is performed, so that the non-aqueous electrolyte is impregnated into the power generating element 40. The exterior body 50 is sealed by applying heat, etc., to obtain the lithium ion secondary battery 100.

[0063] In the lithium ion secondary battery 100 according to the first embodiment, the discharge rate characteristic is improved by adding a small amount of the second active material as a sub-component to the first active material as a main component. The reason for this is not clear, but it is thought that the positive electrode active material layer 24 contains a small amount of the second active material with a different reaction potential, which generates a concentration gradient of Li ions in the active material layer. It is thought that the charge / discharge reaction is promoted by promoting the movement of Li ions according to the concentration gradient of Li ions, thereby improving the discharge rate characteristic. Furthermore, when primary particles are contained in the active material, the discharge rate tends to improve. This tendency is particularly noticeable when the second active material is a primary particle.

[0064] The above describes the embodiments of the present invention in detail with reference to the drawings. However, each configuration and combination thereof in each embodiment is merely an example, and addition, omission, substitution, and other modifications of the configuration are possible without departing from the spirit of the present invention. EXAMPLES

[0065] "Example 1" (Preparation of positive electrode) A positive electrode active material, a conductive material, and a binder were mixed to prepare a positive electrode mixture. The conductive material was carbon black, and the binder was polyvinylidene fluoride (PVDF). The mass ratio of the positive electrode active material, the conductive material, and the binder was 90:5:5. The positive electrode active material was LiNi 0.33 Mn 0.33 Co 0.33 The positive electrode mixture was dispersed in N-methyl-2-pyrrolidone to prepare a positive electrode slurry. Then, a surface area of ​​a 15 μm-thick aluminum foil was coated with the positive electrode mixture so that the coating weight after drying was about 10.0 mg / cm. 2 After coating, the positive electrode slurry was dried at 100° C. to remove the solvent, and a positive electrode active material layer was formed on one side of the aluminum foil. After drying, a positive electrode active material layer was applied to the other side of the aluminum foil so that the weight per unit area after drying was about 10.0 mg / cm.2 After coating, the positive electrode slurry was dried at 100° C. to remove the solvent, thereby forming positive electrode active material layers on both sides of the aluminum foil.

[0066] (Preparation of negative electrode) The negative electrode active material, conductive material, and binder were mixed to prepare the negative electrode mixture. The negative electrode active material was graphite, the binder was styrene-butadiene rubber (SBR), and carboxymethyl cellulose (CMC) was added as a thickener. The mass ratio of the negative electrode active material to the binder and thickener was 95:3:2. This negative electrode mixture was dispersed in distilled water to prepare a negative electrode slurry. Then, the negative electrode mixture was applied to one side of a 10 μm-thick copper foil with a weight of approximately 6.0 mg / cm after drying. 2 After coating, the negative electrode slurry was dried at 100° C. to remove the solvent, and a negative electrode active material layer was formed on one side of the copper foil. After drying, the other side of the copper foil was coated with a negative electrode active material layer having a weight per unit area of ​​about 6.0 mg / cm2 after drying. 2 After coating, the negative electrode slurry was dried at 100° C. to remove the solvent, thereby forming negative electrode active material layers on both sides of the copper foil.

[0067] (Cell Preparation) The negative and positive electrodes were punched out into a predetermined shape, and alternately stacked with 25 μm thick polypropylene separators between them to produce a laminate of nine negative electrodes and eight positive electrodes. The laminate produced in the same manner was cut as a sample, and the morphology of the first active material and the second active material was confirmed by TEM. The first active material was a secondary particle, and the second active material was a primary particle.

[0068] The laminate was inserted into an exterior body of an aluminum laminate film and heat-sealed except for one peripheral portion to form an opening. A non-aqueous electrolyte was injected into the exterior body. The non-aqueous electrolyte was prepared by dissolving 1.5 MOL / L of lithium hexafluorophosphate (LiPF6) in a solvent in which equal amounts of ethylene carbonate (EC) and dimethyl carbonate (DEC) were mixed. The remaining portion was then heat-sealed while reducing the pressure using a vacuum sealer to produce a lithium ion secondary battery according to Example 1.

[0069] (Battery evaluation: discharge rate characteristics) The discharge rate characteristics of the fabricated lithium-ion battery were evaluated. The discharge rate characteristics were determined as the ratio (%) of the discharge capacity at a discharge rate of 3C (current value at which discharge ends in 20 minutes when constant current discharge is performed at 25°C) to the discharge capacity at a discharge rate of 1C (current value at which discharge ends in 1 hour when constant current discharge is performed at 25°C) taken as 100%.

[0070] The discharge rate characteristics of the cell were evaluated at 0.15 mA / cm 2 The actual capacity of the fabricated cell was measured by performing the initial charge and discharge at a current density of 1C. Based on the actual capacity obtained, the current densities for the discharge rates of 1C and 3C were determined.

[0071] After the initial charge and discharge, the battery was charged at a constant current of 0.5 C to 4.3 V, and then charged at a constant voltage of 0.02 C until the current density reached 0.02 V. After a 5-minute rest period, the battery was discharged at a constant current of 1 C to 2.8 V, and the discharge capacity at 1 C was measured. A 5-minute rest period was then taken after the measurement.

[0072] Thereafter, the battery was charged at a constant current of 0.5 C up to 4.3 V, and then charged at a constant voltage up to a current density of 0.02 C. After a 5-minute rest period, the battery was discharged at a constant current of 3 C up to 2.8 V, and the discharge capacity at 3 C was measured.

[0073] "Examples 2 to 5, Comparative Examples 1 and 2" Examples 2 to 5 and Comparative Examples 1 and 2 differ from Example 1 in that the ratio of the first active material to the second active material was changed. Comparative Example 1 consisted of only the first active material. In Comparative Example 1, the first active material was 100.0% and the second active material was 0.0%. In Example 2, the first active material was 99.0% and the second active material was 1.0%. In Example 3, the first active material was 97.0% and the second active material was 3.0%. In Example 4, the first active material was 96.0% and the second active material was 4.0%. In Example 5, the first active material was 96.5% and the second active material was 4.5%. In Comparative Example 2, the first active material was 95.0% and the second active material was 5.0%. The discharge rate characteristics were measured for Examples 2 to 5 and Comparative Examples 1 and 2. Table 1 shows the percentages of the rate characteristics of Examples 2 to 5 and Comparative Example 2 when the rate characteristic of Comparative Example 1 is taken as 100%. In other words, the rate characteristics of Examples 2 to 5 and Comparative Example 2 shown in Table 1 are relative values ​​to the rate characteristic of Comparative Example 1.

[0074] "Examples 6 to 10, Comparative Examples 3 and 4" In Examples 6 to 10 and Comparative Examples 3 and 4, the first active material was LiNi 0.6 Mn 0.2 Co 0.2 This example differs from Examples 1 to 5 and Comparative Examples 1 and 2 in that O2 (referred to as NMC622 in Table 1) was used. The discharge rate characteristics were measured for Examples 6 to 10 and Comparative Examples 3 and 4. Table 1 shows the percentages of the rate characteristics of Examples 6 to 10 and Comparative Example 4 when the rate characteristic of Comparative Example 3 is taken as 100%. In other words, the rate characteristics of Examples 6 to 10 and Comparative Example 4 shown in Table 1 are relative values ​​to the rate characteristic of Comparative Example 3.

[0075] "Examples 11 to 15, Comparative Examples 5 and 6" In Examples 11 to 15 and Comparative Examples 5 and 6, the first active material was LiNi 0.85 Co 0.10 Al 0.05 This example differs from Examples 1 to 5 and Comparative Examples 1 and 2 in that O2 (referred to as NCA in Table 1) was used. The discharge rate characteristics were measured for Examples 11 to 15 and Comparative Examples 5 and 6. Table 1 shows the percentages of the rate characteristics of Examples 11 to 15 and Comparative Example 6 when the rate characteristic of Comparative Example 5 is taken as 100%. In other words, the rate characteristics of Examples 11 to 15 and Comparative Example 6 shown in Table 1 are relative values ​​to the rate characteristic of Comparative Example 5.

[0076] "Examples 16 to 20, Comparative Examples 7 and 8" Examples 16 to 20 and Comparative Examples 7 and 8 differ from Examples 1 to 5 and Comparative Examples 1 and 2 in that LiFePO4 (referred to as LFP in Table 2) was used as the first active material. The discharge rate characteristics were measured for Examples 16 to 20 and Comparative Examples 7 and 8. Table 2 shows the percentages of the rate characteristics of Examples 16 to 20 and Comparative Example 8 when the rate characteristic of Comparative Example 7 is taken as 100%. In other words, the rate characteristics of Examples 16 to 20 and Comparative Example 8 shown in Table 2 are relative values ​​to the rate characteristic of Comparative Example 7.

[0077] "Examples 21 to 25, Comparative Examples 9 and 10" In Examples 21 to 25 and Comparative Examples 9 and 10, the first active material was LiNi 0.8 Mn 0.1 Co 0.1 This example differs from Examples 1 to 5 and Comparative Examples 1 and 2 in that O2 (referred to as NMC811 in Table 2) was used. The discharge rate characteristics were measured for Examples 21 to 25 and Comparative Examples 9 and 10. Table 2 shows the percentages of the rate characteristics of Examples 21 to 25 and Comparative Example 10 when the rate characteristic of Comparative Example 9 is taken as 100%. In other words, the rate characteristics of Examples 21 to 25 and Comparative Example 10 shown in Table 2 are relative values ​​to the rate characteristic of Comparative Example 9.

[0078] "Examples 26 to 30, Comparative Examples 11 and 12" Examples 26 to 30 and Comparative Examples 11 and 12 differ from Examples 1 to 5 and Comparative Examples 1 and 2 in that the first active material was LiCoO2 (referred to as LCO in Table 3) and the second active material was LiMn2O4 (referred to as LMO in Table 3) having a spinel structure. The discharge rate characteristics were measured for Examples 26 to 30 and Comparative Examples 11 and 12. Table 3 shows the percentages of the rate characteristics of Examples 26 to 30 and Comparative Example 12 when the rate characteristic of Comparative Example 11 is taken as 100%. That is, the rate characteristics of Examples 26 to 30 and Comparative Example 12 shown in Table 3 are relative values ​​to the rate characteristic of Comparative Example 11.

[0079] "Examples 31 to 35, Comparative Examples 13 and 14" Examples 31 to 35 and Comparative Examples 13 and 14 differ from Examples 26 to 30 and Comparative Examples 11 and 12 in that the second active material was NMC333. The discharge rate characteristics were measured for Examples 31 to 35 and Comparative Examples 13 and 14. Table 3 shows the percentages of the rate characteristics of Examples 31 to 35 and Comparative Example 14 when the rate characteristic of Comparative Example 13 is taken as 100%. That is, the rate characteristics of Examples 31 to 35 and Comparative Example 14 shown in Table 3 are relative values ​​to the rate characteristic of Comparative Example 13.

[0080] "Examples 36 to 40, Comparative Examples 15 and 16" Examples 36 to 40 and Comparative Examples 15 and 16 differ from Examples 26 to 30 and Comparative Examples 11 and 12 in that the second active material was NMC622. The discharge rate characteristics were measured for Examples 36 to 40 and Comparative Examples 15 and 16. Table 3 shows the percentages of the rate characteristics of Examples 36 to 40 and Comparative Example 16 when the rate characteristic of Comparative Example 15 is taken as 100%. In other words, the rate characteristics of Examples 36 to 40 and Comparative Example 16 shown in Table 3 are relative values ​​to the rate characteristic of Comparative Example 15.

[0081] "Examples 41 to 45, Comparative Examples 17 and 18" Examples 41 to 45 and Comparative Examples 17 and 18 differ from Examples 26 to 30 and Comparative Examples 11 and 12 in that the second active material was LiFePO4 (referred to as LFP in Table 1). The discharge rate characteristics were measured for Examples 41 to 45 and Comparative Examples 17 and 18. Table 4 shows the percentages of the rate characteristics of Examples 41 to 45 and Comparative Example 18 when the rate characteristic of Comparative Example 17 is taken as 100%. That is, the rate characteristics of Examples 41 to 45 and Comparative Example 18 shown in Table 4 are relative values ​​to the rate characteristic of Comparative Example 17.

[0082] "Examples 46 to 50, Comparative Examples 19 and 20" Examples 46 to 50 and Comparative Examples 19 and 20 differ from Examples 1 to 5 and Comparative Examples 1 and 2 in that three types of active materials were used. The first active material was LCO, the second active material was NMC333, and the third active material was NMC622. The abundance ratio of the first active material was fixed at 62%, and the abundance ratio of the second active material and the third active material was changed.

[0083] In Comparative Example 19, the first active material was 62.0%, the second active material was 0.0%, and the third active material was 38.0%. In Example 46, the first active material was 62.0%, the second active material was 0.5%, and the third active material was 37.5%. In Example 47, the first active material was 62.0%, the second active material was 1.0%, and the third active material was 37.0%. In Example 48, the first active material was 62.0%, the second active material was 3.0%, and the third active material was 35.0%. In Example 49, the first active material was 62.0%, the second active material was 4.0%, and the third active material was 34.0%. In Example 50, the first active material was 62.0%, the second active material was 4.5%, and the third active material was 33.5%. In Comparative Example 20, the first active material was 62.0%, the second active material was 5.0%, and the third active material was 33.0%. The discharge rate characteristics were measured for Examples 46 to 50 and Comparative Examples 19 and 20. Table 4 shows the ratios of the rate characteristics of Examples 46 to 50 and Comparative Example 20 when the rate characteristic of Comparative Example 19 is taken as 100%. In other words, the rate characteristics of Examples 46 to 50 and Comparative Example 20 shown in Table 4 are relative values ​​to the rate characteristic of Comparative Example 19.

[0084] [Table 1]

[0085] [Table 2]

[0086] [Table 3]

[0087] [Table 4]

[0088] "Examples 51 to 56" Examples 51 to 53 differ from Example 3 in that the forms of the first active material and the second active material were changed. Examples 54 to 56 differ from Example 8 in that the forms of the first active material and the second active material were changed. The discharge rate characteristics of Examples 51 to 56 were measured. The results are shown in Table 5. The rate characteristics of Examples 51 to 53 in Table 5 are relative values ​​to Comparative Example 1, and the rate characteristics of Examples 54 to 56 are relative values ​​to Comparative Example 3. Table 5 also shows the results of Examples 3 and 8 for comparison.

[0089] [Table 5]

[0090] "Examples 57 to 70" Examples 57 to 63 differ from Example 3 in that the relationship between the particle sizes of the first active material and the second active material was changed. Examples 64 to 70 differ from Example 8 in that the forms of the first active material and the second active material were changed. The discharge rate characteristics of Examples 57 to 70 were measured. The results are shown in Table 6. The rate characteristics of Examples 57 to 63 are relative values ​​to Comparative Example 1, and the rate characteristics of Examples 64 to 70 are relative values ​​to Comparative Example 3. Table 6 also shows the results of Examples 3 and 8 for comparison.

[0091] [Table 6] [Explanation of symbols]

[0092] 10 Separator 20 positive electrode 22 Positive electrode current collector 24 Cathode active material layer 30 negative electrode 32 Negative electrode current collector 34 Negative electrode active material layer 40 Power generating element 50 Exterior body 52 Metal foil 54 Resin layer 60, 62 terminals 100 Lithium-ion secondary battery

Claims

1. At least an active material and a binder; The active material includes a first active material as a main component and a second active material as a subcomponent having a composition different from that of the first active material, A ratio of the first active material is 60% or more and less than 100% of the total active material, The ratio of the second active material is greater than 0% and less than 5% of the total active material, The combination of the first active material and the second active material is The active material layer, wherein the first active material is a nickel-cobalt-manganese ternary compound or a nickel-cobalt-aluminum ternary compound, and the second active material is lithium cobalt oxide.

2. A battery comprising at least an active material and a binder, The active material includes a first active material as a main component and a second active material as a subcomponent having a composition different from that of the first active material, A ratio of the first active material is 60% or more and less than 100% of the total active material, The ratio of the second active material is greater than 0% and less than 5% of the total active material, The combination of the first active material and the second active material is The first active material is a nickel-cobalt-manganese ternary compound or a nickel-cobalt-aluminum ternary compound, and the second active material is lithium cobalt oxide; or The first active material is lithium cobalt oxide, and the second active material is any one selected from the group consisting of a nickel-cobalt-manganese ternary compound, a nickel-cobalt-aluminum ternary compound, and lithium iron phosphate; the first active material is a secondary particle formed by agglomeration of a plurality of primary particles, The active material layer, wherein the second active material is a primary particle.

3. 3. The active material layer according to claim 1, wherein the particle size of the first active material is 0.6 to 1.5 times the particle size of the second active material.

4. A porous medium comprising at least an active material and a binder, The active material includes a first active material as a main component and a second active material as a subcomponent having a composition different from that of the first active material, A ratio of the first active material is 60% or more and less than 100% of the total active material, The ratio of the second active material is greater than 0% and less than 5% of the total active material, The combination of the first active material and the second active material is The first active material is a nickel-cobalt-manganese ternary compound or a nickel-cobalt-aluminum ternary compound, and the second active material is lithium cobalt oxide; or The first active material is lithium cobalt oxide, and the second active material is any one selected from the group consisting of a nickel-cobalt-manganese ternary compound, a nickel-cobalt-aluminum ternary compound, and lithium iron phosphate; The reaction potential of the second active material is higher than the reaction potential of the first active material.

5. The second active material is Li a Co 1-y M y O 2 ...(1) a satisfies 0.8≦a≦1.2 and y satisfies 0≦y<0.5, The active material layer according to any one of claims 1 to 4, wherein M is at least one of Ni, Mn, Fe, Mg, Zr, Al, Ti, Zn, Cu, Ca, and Na.

6. A current collector; An electrode comprising: the active material layer according to any one of claims 1 to 5 laminated on at least one surface of the current collector.

7. A lithium ion secondary battery comprising the electrode of claim 6.

Citation Information

Patent Citations

  • Lithium secondary battery

    JP1996236114A

  • Battery

    JP1999016566A

  • Positive electrode active material for lithium secondary battery

    JP2003217572A

  • Lithium ion secondary battery

    JP2006294393A

  • Nonaqueous electrolyte secondary battery

    JP2008034218A